1996
DOI: 10.1063/1.362801
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Ni90Ti10 alloy thin film with 6H-SiC single crystal

Abstract: Interfacial reactions, phase formation, microstructure, and composition, as functions of heat treatments (400–800 °C) were investigated in Ni90Ti10 alloy thin film coevaporated on an n-type 6H-SiC (0001) single-crystal substrate. The study was carried out with the aid of Auger electron spectroscopy, x-ray diffraction, and analytical transmission electron microscopy. The interaction was found to begin at 450 °C. Ni and C are the dominant diffusing species. The reaction zone is divided into three layers. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…According to the ternary phase diagram in the Ni-Si-C system at 850uC, only Ni 2 Si can be in equilibrium with both C and SiC. 11 The reaction is thus…”
Section: Resultsmentioning
confidence: 99%
“…According to the ternary phase diagram in the Ni-Si-C system at 850uC, only Ni 2 Si can be in equilibrium with both C and SiC. 11 The reaction is thus…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the improvement of the barrier homogeneity can be explained by the formation of nickel silicide (Ni 2 Si), which starts to form after annealing at 600°C by reaction of nickel with silicon carbide. At this temperature and for short annealing time, however, the Ni 2 Si phase still coexists with the Ni 31 Si 12 , which is the first phase forming in the reaction of the Ni-Si-C system because of its more negative hentalpy [9]. As consequence of the presence of both Ni 31 Si 12 and Ni 2 Si at 600°C, a wide distribution of the Schottky barrier heights is observed.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, the direct reaction between Ni and Si is also exothermic. 33 Consequently, beyond decreasing grain sizes and improving dielectric properties, Ni may also have an active role in promoting the combustion synthesis of SiC.…”
Section: Discussionmentioning
confidence: 99%
“…38 Nevertheless, it has been reported that Ni does not easily form stable carbides. 33,39,40 Therefore, SiC nuclei (Eq. [1]) should predominantly form and be dispersed in the bulk of the droplet, which subsequently grows to form SiC grains.…”
Section: May 2011mentioning
confidence: 99%